OTH-004 Blue light imaging for optical diagnosis of colorectal polyps: the impact of a training intervention. (8th June 2018) - Subramaniam, Sharmila; Alkandari, Asma; Kandiah, Kesavan; Smith, Rebecca; Stammers, Matthew; Thayalasekaran, Sreedhari; Aepli, Patrick; Hayee, Bu'; Schoon, Erik; Stefanovic, Milan; Bhandari, Pradeep
Abstract : Introduction: The advent of image enhanced endoscopic modalities have paved the way for better optical diagnosis of colorectal polyps. Blue Light Imaging (BLI) is a new technology that utilises powerful light emitting diode technology to enhance mucosal surface and vessel patterns. A specific BLI classification has recently been developed to enable better characterisation of colorectal polyps (BLI Adenoma Serrated International Classification - BASIC): The aim of our study was to investigate the diagnostic ability of BLI before and after training using this classification in experienced and non-experienced endoscopists. Methods: BLI images from 45 polyps were shown to 10 endoscopists (5 with experience of advanced endoscopic imaging and 5 trainees with limited experience). They independently classified each of the images as adenoma or hyperplastic initially without any focused training on interpretation of BLI images. A training module on BASIC was developed and each endoscopist undertook a face to face training session where direct feedback was given. All endoscopists then repeated the image classification exercise. The sensitivity, specificity, accuracy, negative (NPV) and positive predictive value (PPV) for adenoma detection was calculated. Results: In both groups of endoscopists, there was a significant improvement in sensitivity and NPV of adenoma detection (p<0.05) following training and utilisation of a dedicated BLI classification system (see table below). This improvement was greater in the experienced endoscopist cohort where overall higher accuracy rates were achieved with no decrease in specificity. Conclusions: The use of a bespoke BLI classification system with adequate training can significantly improve the sensitivity and NPV of adenoma detection in both experienced and non-experienced endoscopists thereby enabling the full potential of this novel imaging technology to be realised.